2010
DOI: 10.1007/s00383-010-2613-6
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric gastric outlet obstruction following corrosive ingestion

Abstract: GOO is one of the most common gastric complications of corrosive ingestion that may require surgical treatment. Prevention of corrosive ingestion has great importance to avoid such complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 16 publications
0
27
0
6
Order By: Relevance
“…Pyloric obstruction can develop after gastric lesions, especially due to the ingestion of acidic agents after 3-7 weeks (8,10,24,25). In our series, one of the patients who had a history of acidic agent (thinner) ingestion developed a gastric outlet stricture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyloric obstruction can develop after gastric lesions, especially due to the ingestion of acidic agents after 3-7 weeks (8,10,24,25). In our series, one of the patients who had a history of acidic agent (thinner) ingestion developed a gastric outlet stricture.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, one of the patients who had a history of acidic agent (thinner) ingestion developed a gastric outlet stricture. Isolated gastric strictures are relatively rare and arise essentially due to acid ingestion (24,26). The reported rate of esophageal stricture development is 9%-18% (8).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that gastric injury and PS usually occur in cases of acidic ingestion; it has been reported that the incidence of PS secondary to alkaline ingestion may differ [1,[9][10][11]. The caustic substances ingested by almost all of the patients in the present study were acidic except one.…”
Section: Discussionmentioning
confidence: 51%
“…Selection of surgical techniques and appropriate timing are controversial topics. Previous studies have recommended pyloroplasty, gastroduodenostomy, and partial or total gastrectomy, based on the location and extent of gastric injury [9][10][11]14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation